Repeated Sulforaphane Treatment Reverses Depressive-like Behavior and Exerts Antioxidant Effects in the Olfactory Bulbectomy Model in Mice - Patrycja Pańczyszyn-Trzewik; Katarzyna Stachowicz; Paulina Misztak; Gabriel Nowak; Magdalena Sowa-Kućma (MDPI AG, 2024)
Growing evidence suggests that activators of nuclear factor erythroid-derived 2-like 2 (Nrf2), such as sulforaphane, may represent promising novel pharmacological targets for conditions related to oxidative stress, including depressive disorder. Therefore, we conducted a study to explore the behavioral and biochemical effects of repeated (14 days) sulforaphane (SFN) treatment in the olfactory bulbectomy (OB) animal model of depression. An open field test (OFT), splash test (ST), and spontaneous locomotor activity test (LA) were used to assess changes in depressive-like behavior and the potential antidepressant-like activity of SFN. The OB model induced hyperactivity in mice during the OFT and LA as well as a temporary loss of self-care and motivation in the ST. The repeated administration of SFN (10 mg/kg) effectively reversed these behavioral changes in OB mice across all tests. Additionally, a biochemical analysis revealed that SFN (10 mg/kg) increased the total antioxidant capacity in the frontal cortex and serum of the OB model. Furthermore, SFN (10 mg/kg) significantly enhanced superoxide dismutase activity in the serum of OB mice. Overall, the present study is the first to demonstrate the antidepressant-like effects of repeated SFN (10 mg/kg) treatment in the OB model and indicates that these benefits may be linked to improved oxidative status.